The Gene Rearrangement, Loss, Transfer, and Deep Intronic Variation in Mitochondrial Genomes of Conidiobolus - Nie, Yong; Zhao, Heng; Wang, Zimin; Zhou, Zhengyu; Liu, Xiaoyong; Huang, Bo (Frontiers in Microbiology, 2021)
The genus Conidiobolus s.s. was newly delimited from Conidiobolus s.l. In order to gain insight into its mitochondrial genetic background, this study sequenced six mitochondrial genomes of the genus Conidiobolus s.s. These mitogenomes were all composed of circular DNA molecules, ranging from 29,253 to 48,417 bp in size and from 26.61 % to 27.90 % in GC content. The order and direction for 14 core protein-coding genes (PCGs) were identical, except for the atp8 gene lost in C. chlamydosporus, C. polyspermus and C. polytocus, and rearranged in the other Conidiobolus s.s. species. Besides, the atp8 gene split the cox1 gene in C. taihushanensis. Phylogenomic analysis based on the 14 core PCGs confirmed that all Conidiobolus s.s. species formed a monophyly in the Entomophthoromycotina lineage. The number and length of introns were the main factors contributing to mitogenomic size, and deep variations and potential transfer were detected in introns. In addition, gene transfer occurred between the mitochondrial and nuclear genomes. This study promoted the understanding of the evolution and phylogeny of the Conidiobolus s.s. genus.